What does lexical creativity have to say about the Covid-19 pandemic? The case of French - Jacquet-Pfau, Christine (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
The COVID-19 pandemic, with its medical, economic and social implications, provides a unique opportunity to investigate the endless creativity it gave rise to in all areas, including language, showing just how society can cope with a crisis situation unprecedented in its duration and seriousness. The analysis carried out in this paper shows what lexical resources French provided to put into words a situation which utterly transformed behaviour and social norms. Certain typical keywords have been selected for analysis from the latest edition of a general language reference dictionary, Le Petit Larousse illustré 2022, including neologisms of meaning (confinement), neologisms of form (quatorzaine), direct or indirect loans and equivalents proposed (COVID-19, distanciation sociale…). There are no playful occasionalisms to speak of in the dictionary corpus. The impact of the crisis situation on the reception of loanwords from English is also evaluated.